PEMBERDAYAAN CAREGIVERS MELALUI KEGIATAN PELATIHAN SKT (SOMPORN KANTARADUSSADEE TRIAMCHAISRI) SEBAGAI BAGIAN PERAWATAN JANGKA PANJANG BAGI LANSIA DI WILAYAH KELURAHAN PEDUNGAN - Agustini, Ni Luh Putu Inca Buntari; Suyasa, I Gede Putu Darma; Kamaryati, Ni Putu; Diyu, Ida Ayu Ningrat Pangruating; Agustini, Ni Komang Tri; Krisnandari, Anak Agung Istri Wulan; Putra, I Nyoman Arya Maha (Community Development in Health Journal, 2023)
Introduction & Aim: Long-term care is provided for the elderly who experience limitations in carrying out independent physical activities. Caregivers as an important role in accompanying the elderly and families who experience limited independence due to chronic illnesses. Innovation is needed to equip caregivers to provide optimal health services. One of the long-term care has been shown by implementing SKT (Somporn Kantharadussadee Triamchaisri) for the elderly with chronic health conditions and physical limitations. The purpose of this activity is to disseminate SKT to the community through training for caregivers to achieve a better quality of life for the community in Pedungan Health Village. Method of Activity: The stages of this community project use the POAC concept approach, namely Planning by conducting assessments with partners regarding activities, Organizing through approaches with related parties, such as bringing in experts in the field of HCS from Thailand, conducting TOT at ITEKES Bali for the sustainability of HCS in Bali, readiness analysis caregivers in receiving SKT training. Actuating and Controlling conducted training for caregivers related to HCS, evaluation, and reflection which were carried out 4 times in June 2023. Results: These activity results showed that the results of the HCS training had an impact on changes in SpO2, blood pressure, and blood sugar over time. Discussion: This simple exercise pattern makes SKT a safe choice for those with chronic health conditions and physical limitations and for the elderly who need long-term care.